FREQUENCY OF FEBRILE NEUTROPENIA IN ELDERLY PATIENTS OF DIFFUSE LARGE B CELL LYMPHOMA RECEIVING MODIFIED DOSE CHOP REGIMEN OF CHEMOTHERAPY - Tanvir Ahmed; Tahir Mehmood; Shahbaz Ahmed; Muhammad Akram; Tehreem Fatima (Journal of University Medical & Dental College, 2019)
Objective: To determine the frequency of febrile neutropenia in elderly patients of diﬀuse large B cell lymphoma receiving modiﬁed dose CHOP regimen of chemotherapy. Material and Methods: This descriptive case series study was conducted on 140 Patients of diﬀuse large B-cell lymphoma at Department of Oncology Jinnah Hospital Lahore from May 2018 to October 2018. The patients aged 60-85 years and of either gender presenting with diﬀuse large B- cell lymphoma were included. Patients who have received any other treatment (chemotherapy, radiotherapy) prior to presentation and IHD were excluded. Selected patients received almost two- third dose of standard CHOP protocol, cyclophosphamide 750 mg/m2, doxorubicin 50 mg/m2, and vincristine 1.4 mg/m2 (maximum dose, 2.0 mg), all given intravenously on day 1, together with prednisone 60-100 mg/m2 PO on days 1-5, administered every 21 days. Frequency of febrile neutropenia was checked after cycle 1 of CHOP. Results: Mean age was 70.6±5.6 years. Majority of the patients 81 (57.9%) were between 60 to 70 years of age. Out of the 140 patients, 83 (59.3%) were male and 57 (40.7%) were females with male to female ratio of 1.5:1. In this study, frequency of febrile neutropenia in elderly patients of diﬀuse large B cell lymphoma receiving modiﬁed dose CHOP regimen of chemotherapy was found in 80 (57.1%) patients. Conclusion: This study concluded that the frequency of febrile neutropenia in elderly patients of Diﬀuse large B cell lymphoma receiving modiﬁed dose CHOP regimen of chemotherapy is quite high.